2007
DOI: 10.1016/j.ijgo.2006.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Emergency peripartum hysterectomy in the nulliparous patient

Abstract: Though rare, peripartum hysterectomy in the nulliparous patients carries high maternal morbidity and perinatal mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Our EPH incidence of 0.39 per 1,000 deliveries compares favourably with those quoted from developed countries [2,3,4,5,6]. Much higher rates of 2.7 per 1,000 deliveries have been reported from developing countries [7,8,9,10]. The cutoff point at which hysterectomy becomes necessary is subjective and ill-defined.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our EPH incidence of 0.39 per 1,000 deliveries compares favourably with those quoted from developed countries [2,3,4,5,6]. Much higher rates of 2.7 per 1,000 deliveries have been reported from developing countries [7,8,9,10]. The cutoff point at which hysterectomy becomes necessary is subjective and ill-defined.…”
Section: Discussionsupporting
confidence: 61%
“…The incidence of EPH varies from 0.3 to 1.6 per 1,000 deliveries in developed countries [2,3,4,5,6] and may be higher in developing countries [7,8]. The purpose of this preliminary study in Kuwait was to estimate the incidence, indications, risk factors and complications associated with EPH performed in a tertiary teaching hospital in Kuwait.…”
Section: Introductionmentioning
confidence: 99%
“…One patient died due to hemorrhagic shock from a ruptured uterus, and 3 patients died due to sepsis after being referred from periphery of the city after obstructed labor. Compared to a study in Ghana, “there were no maternal deaths but there were 7 near-missed fatalities”; whereas a study in Maryland noted 2 deaths in 34 patients from 1991 to 2001 [4, 5]. A study done at another tertiary care facility in another city of Pakistan noted maternal mortality in 4 (19%) of their cases [6].…”
Section: Resultsmentioning
confidence: 99%
“…In Africa the most common aetiologies include uterine rupture, atonic uteri and sepsis. [14,19,[29][30][31] Three studies performed in tertiary care settings in South Africa (SA) have shown particularly high rates of sepsis. A study performed in Mthatha showed that uterine atony, puerperal sepsis and secondary postpartum haemorrhage made up 57% of the indications.…”
mentioning
confidence: 99%